2006
DOI: 10.1111/j.1365-2915.2006.00631.x
|View full text |Cite
|
Sign up to set email alerts
|

Oral myiasis in a child by the reindeer warble fly larva Hypoderma tarandi

Abstract: We describe a case of human oral myiasis by a first-stage larva of the reindeer warble fly, Hypoderma (Oedemagena) tarandi (L.) (Diptera: Oestridae), in a 12-year-old girl. In September the patient complained of erythema, swelling and conjunctivitis of the right eyelid. Symptoms subsided spontaneously but re-occurred in October. In December she presented with acute swelling of the right corner of the mouth. Later that day a living larva protruded from this swelling. The patient had been on vacation in Norway d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 4 publications
2
17
0
Order By: Relevance
“…in Spain occurred in children who spent time in rural areas (Martinón et al, 1974). Case reports also suggested that infections by H. tarandi are more frequent in tourists on holidays in Northern Scandinavia than in Sami reindeer herders or in local populations from reindeer breeding areas (Faber and Hendrikx, 2006). Whether this observation is a consequence of the lack of referral to medical authorities or to the development of protective immune responses in these populations (Kearney et al, 1991;Kan et al, 2010), remains to be elucidated.…”
Section: Predisposing Factorsmentioning
confidence: 93%
See 2 more Smart Citations
“…in Spain occurred in children who spent time in rural areas (Martinón et al, 1974). Case reports also suggested that infections by H. tarandi are more frequent in tourists on holidays in Northern Scandinavia than in Sami reindeer herders or in local populations from reindeer breeding areas (Faber and Hendrikx, 2006). Whether this observation is a consequence of the lack of referral to medical authorities or to the development of protective immune responses in these populations (Kearney et al, 1991;Kan et al, 2010), remains to be elucidated.…”
Section: Predisposing Factorsmentioning
confidence: 93%
“…Self-cure from Hypoderma spp. larvae (i.e., abortive infection), has also been reported (Faber and Hendrikx, 2006). Immunological tests may assist indirect diagnoses.…”
Section: Diagnosismentioning
confidence: 96%
See 1 more Smart Citation
“…Therefore, these diseases should be included in the differential diagnosis of severe oral myiasis. The number of maggots can range from one to several hundred, depending on the stage of the infection and the infective species (Figures ) …”
Section: Clinical Featuresmentioning
confidence: 99%
“…The number of maggots can range from one to several hundred, depending on the stage of the infection and the infective species (Figures 1-3). 24,27,28…”
Section: Clinical Featuresmentioning
confidence: 99%